PROTOTYPE OF SMALLHOLDER COCOA FARM BASED ON ORGANIC AGRICULTURE : LESSON FROM CENTRAL SULAWESI, INDONESIA - Mohamad Yunus; Danang Widjayanto; sisfah yuni; Marwan Yantu (AGROLAND: The Agricultural Sciences Journal, 2014)
Yantu et al. developed the prototype of smallholder cocoa farm. The aim of this study is (i)  to test effect of application of biological agent to productivity of cocoa farm; and (ii) to test workability of the prototype based on the application. Design of the research was completely random design. There were 4 treatments for every object (cocoa black pod (CBP), vascular streak dieback (VSD), and pod borer (PB), 6 repetition, and 4 observation times. The result of analyzes showed that the treatments significantly effect to the decreasing of attack level of CBP, VSD and PB at level of alpha 0.05. The result of Tukey’s method showed that two treatments significantly difference from control, namely P2 (spraying with Trichoderma sp. for CBP and VSD, and with   B. bassiana for PB), and P3 (spraying with Trichoderma sp. and giving compost plus Trichoderma sp. for CBP and VSD, and with B. bassiana giving compost plus Trichoderma sp. for PB). Iterating the primary data of the treatments both to the prototype can be predicted event of decreasing of pod damage, namely 75 – 93 percents. That signed that the prototype put to a test its workability.      The hypothesis value for decreasing was just 35.69 percent. In consequence of the decreasing is the increasing of the productivity minimal 3.36 in magnitude.Key Words : Organic agriculture, method of learning by doing, participatory approach, prototype of smallholder cocoa farm.